A Review of the Research in Emotionally Focused Therapy for Couples. Issue 3 (8th June 2016) - Wiebe, Stephanie A.; Johnson, Susan M.
Abstract : Emotionally Focused Therapy for Couples (EFT) is a brief evidence‐based couple therapy based in attachment theory. Since the development of EFT, efficacy and effectiveness research has accumulated to address a range of couple concerns. EFT meets or exceeds the guidelines for classification as an evidence‐based couple therapy outlined for couple and family research. Furthermore, EFT researchers have examined the process of change and predictors of outcome in EFT. Future research in EFT will continue to examine the process of change in EFT and test the efficacy and effectiveness of EFT in new applications and for couples of diverse backgrounds and concerns.